Eksplorasi Lichen Di Sepanjang Jalan Raya Solo Tawangmangu Dan Kawasan Hutan Sekipan Karanganyarjawa Tengah - Furi, Ade Ratna; , Efri Roziaty, S. Si., M. Si (2016)
Research on eksploration of lichen along the highway solo Tawangmangu and forest areas Sekipan Karanganyar Central Java has been carried out in January until February 2016. The research aimed to identify species of lichen in the road of Solo-Tawangmangu and Sekipan Forest. This research was using qualitative descriptive with survey techniques. This method established two stations were stations 1 (Along the Road Solo Tawangmangu) and station 2 (in the forest Sekipan). The research found 18 species of identification of lichen. Five family that Parmeliaceae (4 species), Peltigeraceae (1 species), Physciaceae (4 species), Graphidaceae (4 species), and Calicaceae (5 species). Type morphology was the dominant type of foliose as many as 8 species followed fruticose type 1 species, the type squamulose 5 species and 4 species of crustose type. The percentage of lichen on the second station obtained Physconia sp. 2 (the lowest) equal to 36% at station 1 and Peltigera colina (the highest ) species that 90% at station 2. The traffic density at station 1 was very crowded It influenced the growth of lichen. At station 2 (Sekipan forest) there was no influence of air pollution. So the growth of the lichen were very diver. The percentage of lichen coverage was the highest in Station 1 (90 %) was Peltigera colina and the lowest one was the Road of Solo - Tawangmangu (36 %) was Physconia sp 2.